PERBEDAAN KEBERHASILAN TINGKAT POLIPLOIDISASI IKAN MAS (Cyprinus carpio Linn.) MELALUI KEJUTAN PANAS - Akhmad Taufiq Mukti (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
The easiest, cheapest, simpliest and efficient polyploidization method was heat shock treatment. Each fish species has different tolerance either initial time, temperature or duration of heat shock. The aim of this study were to show and determine the heat shock effects on differentiation of hatching rate, abnormality, survival rate, and successful polyploidization of common carp. The method that used in this study was experiment. Treatment that used was heat shock 40° C during 1.5 minutes of common carp eggs to 3 and 29 minutes after fertilization. Ten replicates were carried out for each treatment. Parameters test were hatching rate, abnormality, survival rate and polyploidy induction by counting of nucleolus number. Data analysis that used was descriptive. The result of this study indicated that heat shock treatment influenced on hatching rate, abnormality, survival rate and polyploidy induction of the common carp polyploidization. Hatching rate of common carp, triploidy and tetraploidy were 22.63 ± 8.36% and 11.10 ± 8.60%, abnormality 13.81 ± 4.67% and 24.86 ± 8.37%, survival rate 52.64 ± 8.46% and 55.04 ± 8.15% and polyploidy induction 70 ± 7.07% and 60 ± 7.07%, respectively.